Reliability Assessment of the Iraqi National Communication Network - Musaria Kareem Mahmood; Fawzi Mohammad Munir Al-Naima; Zahraa Zaidan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
The design of communication networks continues to progress rapidly in more suitable forms to meet the challenges of the present era. This paper presents a tentative study of the design of a reliable Iraqi National Communication Network (INCN). The INCN connects all major cities in Iraq with Baghdad as the central node. The followed subjected procedure is a general method which can be applied to all similar problems concerning any Wide Area Network design.  An optimal backbone is first designed by Prim’s algorithm which has distances between cities as input data. The INCN is subjected to reliability improvement by adding links to the initial backbone. An improved algorithm based on tie-sets method is developed for network reliability computation. Three chosen scenarios (Net1, Net2, and Net3) for the INCN are presented and underwent reliability estimation. Evaluation results show a successive improvement of the network reliability to yield to an optimal solution recognized as being Net3. The adopted topology for the INCN is based on two clusters having Baghdad as the common head cluster. Clustering will simplify the reliability evaluation by decreasing the number of tie-sets, and hence the computation complexity.